Hydroxypropyl Cellulose Methacrylate as a Photo‐Patternable and Biodegradable Hybrid Paper Substrate for Cell Culture and Other Bioapplications. Issue 4 (29th August 2013) - Qi, Aisha; Hoo, Siew Pei; Friend, James; Yeo, Leslie; Yue, Zhilian; Chan, Peggy P. Y.
<x xml:space="preserve">Abstract</x> In addition to the choice of appropriate material properties of the tissue construct to be used, such as its biocompatibility, biodegradability, cytocompatibility, and mechanical rigidity, the ability to incorporate microarchitectural patterns in the construct to mimic that found in the cellular microenvironment is an important consideration in tissue engineering and regenerative medicine. Both these issues are addressed by demonstrating a method for preparing biodegradable and photo‐patternable constructs, where modified cellulose is cross‐linked to form an insoluble structure in an aqueous environment. Specifically, hydroxypropyl cellulose (HPC) is rendered photocrosslinkable by grafting with methylacrylic anhydride, whose linkages also render the cross‐linked construct hydrolytically degradable. The HPC is then cross‐linked via a photolithography‐based fabrication process. The feasibility of functionalizing these HPC structures with biochemical cues is verified post‐fabrication, and shown to facilitate the adhesion of mesenchymal progenitor cells. The HPC constructs are shown to be biocompatible and hydrolytically degradable, thus enabling cell proliferation and cell migration, and therefore constituting an ideal candidate for long‐term cell culture and implantable tissue scaffold applications. In addition, the potential of the HPC structure is demonstrated as an alternative substrate to paper microfluidic diagnostic devices for protein and cell assays.